Analysis of Scratch Software in Scientific Production for 20 Years: Programming in Education to Develop Computational Thinking and STEAM Disciplines - Dúo-Terrón, Pablo (Education Sciences, 2023)
Scratch is an educational software based on visual programming blocks. It was created in 2003 by the Massachusetts Institute of Technology Media Lab (MIT) and it develops computational thinking (CT) skills from an early age in schools and allows STEM (science, technology, engineering and mathematics) projects to be carried out. The aim of this research is to know the development of the scientific production of the Scratch programme in the educational field in scientific articles in WoS and its link with the STEM field. The methodology used in this study is of a bibliometric nature with an analysis of the development in the scientific literature and co-words. The Scratch in Education (Scratch-EDU) programme has been studied using the Web of Science (WoS) database. WoS, Vosviewer and SciMAT were used to extract the results and a total of 579 manuscripts were analysed. The results of the study show that the first scientific article on Scratch published in WoS dates back to 2004, although it is from 2011 when a considerable volume of studies began to appear in the scientific literature, and moreover, in recent years the scientific literature relates Scratch-EDU with topics and keywords related to the STEM field. The conclusions of the study are that the Scratch programme has had a progressive evolution in the scientific field related to education from 2012 to 2020, mainly in proceedings papers, with a decrease in manuscripts in the last two years. The emerging themes and keywords that have most influenced Scratch-EDU manuscripts in recent years are related to the terms “Implementation” and “Curriculum”, connected in turn, with terms such as “pedagogy”, “public school” or “students”. Another term that stands out in the development of scientific evolution is “Computational Thinking”, associated with topics such as “Primary Education”, “Learning” or “Problem Solving”. Finally, a discussion and conclusion of the results has been carried out, which can serve as a turning point for future lines of research on programming and CT in the STEM field from an early age in education.
Keywords: computational thinking; education; SciMAT; Scratch; STEAM; STEM; Web of Science; Scopus; Emerging